International consensus on methodological issues in standardization of fecal calprotectin measurement in inflammatory bowel diseases. Issue 4 (7th May 2021) - D'Amico, Ferdinando; Rubin, David T.; Kotze, Paulo Gustavo; Magro, Fernando; Siegmund, Britta; Kobayashi, Taku; Olivera, Pablo A.; Bossuyt, Peter; Pouillon, Lieven; Louis, Edouard; Domènech, Eugeni; Ghosh, Subrata; et al.
Abstract: Background: Fecal calprotectin (FC) is a non‐invasive marker of gut inflammation which is frequently used to guide therapeutic decisions in patients with inflammatory bowel diseases (IBD). Each step of FC measurement can influence the results, leading to misinterpretations and potentially impacting the management of IBD patients. To date, there is high heterogeneity between FC measurements and no current method is universally accepted as a standard. Aims: Our aim was to provide clear position statementsabout the pre‐analytical and the analytical phases of FC measurement to homogenize FC levels and to minimize variability and risk of misinterpretation through aninternational consensus. Materials & Methods: Fourteen physicians with expertise in the field of IBD and FC from 11 countries attended a virtual international consensus meeting on July 17th, 2020. A systematic literature was conducted and the literature evidence was shared and discussedamong the participants. Statements were formulated, discussed, and voted. Statements were considered approved if all participants agreed. Results: Nine statements were formulated and approved. Based on the available evidence, quantitative tests should be preferred for measuring FC. Furthermore, FC measurement, if possible, should always be performed with the same method and factors influencing FC levels should be taken into account when interpreting the results. Discussion: FC has an increasingly important role in the management of patients with IBD. However, large multicenter studies should be conducted to define the reproducibility and to confirm the diagnostic accuracy of the available FC tests. Conclusion: FC concentrations guide clinicians' treatment decisions. Our statements have a relevant impact in daily practice and could be applied in clinical trials to standardize FC measurement. Key Summary: Summarise the established knowledge on this subject. ‐ FC is a surrogate non‐invasive marker of gut inflammation. ‐ FC is closely correlated with endoscopic and histological activity of disease. ‐ High variability exists between FC measurements. ‐ There is no globally accepted cut‐off of FC. What are the significant findings of this study? ‐ Stool consistency can influence FC extraction. ‐ Quantitative tests are recommended for FC measurement. ‐ Serial FC measurement in an individual patient should be performed with the same FC test. ‐ Interpretation of FC measurement results should include the evaluation of factors that may influence the test.